PENGALAMAN SEKSUALITAS PEREMPUAN PASCA TAH BSO (TOTAL ABDOMINAL HYSTERECTOMYBILATERAL SALPINGO OOPHORECTOMY) - Ramdya Akbar Tukan; Tintin Sukartini; Esti Yunitasari (Jurnal Ilmiah Kesehatan, 2017)
Total Abdominal Bilateral Hysterectomy Salpingo Oophorectomy (TAH BSO) is one of the operations of gynecology which aims to remove the uterus, cervix and both tube and ovarian tubes. This study aims to explore the experience of female sexuality after the operation of TAH BSO at Haji Surabaya Hospital. Methods: This study used in-depth interview method to 7 participants who have conducted TAH BSO at Haji Surabaya Hospital. Result and analysis: This study result 2 findings: (1) Sexual activity after TAH BSO, Most patients experience a decrease in sexual desire, lubrication and lack of intensity sexual intercourse, but there are patients who can feel orgasm during sexual intercourse, (2) The response to the problem faced is husband's positive support and reduce the frequency of intercourse. Discuss and Conclution: This study yielded 2 conclusions: (1) Patients after TAH BSO experience decreased sexual activity such as decreased sexual desire, lubrication, decreased quality of sexual relations, but there are patients who do not feel any lubrication and still can be feel the orgasm, It is caused by a good psychological condition,(3) Patients need the attention of husband and family. Suggestions for further research need to make more in-depth observations of the husband and the patient's family